Jung, Julius Spier, and Palmistry. (2nd January 2020) - Nagel, Alexandra
ABSTRACT: Modern hand-readers regularly refer to C. G. Jung because they believe that Jung endorsed the art of reading hands and practiced it himself. This is a myth. Jung was, however, impressed by the hand-reader Julius Spier (1887–1942) and endorsed his work. Spier introduced a Jungian form of hand-reading, which he called psychochirology, in Berlin in 1929. Psychochirology spread all over the world after Hitler rose to power, when Spier and several of his Jewish students left the country. Spier became an important figure in the life of the Jewish diarist Etty Hillesum (1914–1943). Hand-reading is considered a pseudoscience and, consequently, hand-readers are often not taken seriously, and even famous hand-readers have been forgotten over time. Through the popularity of Hillesum's work, Spier's name has remained alive. He is "upgraded" time and again by the reference that he was one of Jung's pupils.